Role of amniotic membrane transplantation in ocular surface disorders - Arya, SK; Bhala, S; Malik, A; Sood, S (Nepalese Journal of Ophthalmology, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The advent of amniotic membrane (AM) and limbal stem cell grafts have transformed the treatment of diseases resulting in ocular surface failure. The current success may be attributed to cryopreservation of human AM, which retains its properties and renders the amniotic epithelial cells nonviable and thus nonimmunogenic. Its unique properties have prompted its application in a large number of ocular ailments. The present article reviews the properties of AM and its uses in ophthalmic practice. Keywords: amniotic membrane transplantation; ocular surface disorders; chemical injury; dry eye DOI: 10.3126/nepjoph.v2i2.3722 Nep J Oph 2010;2(2) 145-153